KAJIAN MODEL PERBAIKAN KERUSAKAN PERKERASAN KAKU (RIGID PAVEMENT)DI PROVINSI LAMPUNG (Studi Kasus Ruas Jalan Sp. Pematang – Sp. Bujung Tenuk) - Novie Winarny (UNIVERSITAS LAMPUNG, 2012)
A case study to Sp. Pematang – Sp. Bujung Tenuk state road (002 ; The Regulation of Minister ofPublic Works No. 631/KPTS/M/2009 on December 31 st, 2001 about the status and function ofState Road/ Non-Toll Road) included to Arterial Road of Eastern (Trans Asean Highway plan).The increasing of LHR volume and traffic weight has caused severe damages in certain parts.Those damages had been repaired by rigid pavement, by using concrete K-350 with 25 centime-ters thickness, 3.50 M x 5.00 M segmentation. After 4 years, the concrete pavement broke, thedamages are cracks on the edges, strips/lengthways, splits, vanish and perforated. Based on themodel of rigid pavement structure, figured out that the tendency of need of additional reinforce-ment on the edge of the plate, so the weight will not only be borne by concrete plate and dowerbars. The position of vehicle wheels were in the center or plate (Model 2), which affect negativelyto concrete plate with maximal moment as 7715.53 kgr.m and so additional reinforcement (plaitreinforcement) of D12-125 mm was needed. The better quality of concrete, the smaller deflectionwill be. By using fy = 400 MPA, but a conversion could be done for lower quality concrete case inorder to get proper reinforcement’s wide. That’s why the repair advice concentrate to not only onone segment of concrete plate, but also only on damages by giving additional reinforcement (wiremesh) D12 -200 mm (Model 2). To reach the increasing point of concrete tensile stress, the addi-tional reinforcement (wire mash) is needed, depending on damages repair.